2011
DOI: 10.1038/hdy.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale population genetic structure and sex-biased dispersal in the smooth snake (Coronella austriaca) in southern England

Abstract: Human-induced alteration of natural habitats has the potential to impact on the genetic structuring of remnant populations at multiple spatial scales. Species from higher trophic levels, such as snakes, are expected to be particularly susceptible to land-use changes. We examined fine-scale population structure and looked for evidence of sex-biased dispersal in smooth snakes (Coronella austriaca), sampled from 10 heathland localities situated within a managed coniferous forest in Dorset, United Kingdom. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 64 publications
4
39
2
Order By: Relevance
“…Based on biparentally inherited microsatellite loci, Pernetta et al . () suggested sex‐biased dispersal in the species. Taking the results of their study into consideration, we chose to determine the genetic structure of the species on the basis of both biparentally and uniparentally (maternally) inherited markers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on biparentally inherited microsatellite loci, Pernetta et al . () suggested sex‐biased dispersal in the species. Taking the results of their study into consideration, we chose to determine the genetic structure of the species on the basis of both biparentally and uniparentally (maternally) inherited markers.…”
Section: Introductionmentioning
confidence: 97%
“…This is not attributed to a lack of interest in the species but, instead, to the fact that C. austriaca is not easy to study as a result of its secretive mode of life and low densities in a number of areas within its geographical distribution (Sewell et al ., ). To date, only two studies based on molecular markers have been conducted for the species: one based on microsatellite markers that evaluated the fine‐scale population differentiation in one locality in Great Britain (Pernetta et al ., ) and the other using mitochondrial cytochrome b sequences to elucidate the phylogeography of the species, mostly focusing on the south‐western edge of its range (Santos et al ., ), where two subspecies have been distinguished: Coronella austriaca acutirostris in the north of Iberian Peninsula, and Coronella austriaca fitzingeri in southern Italy and Sicily (Arnold & Ovenden, ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this contrasted pattern was not previously observed in marine tetrapods or in any snake species. Instead, strong phenotypic and genetic structuring effects caused by local factors have previously been documented in snakes (Kuriyama et al ., ; Pernetta et al ., ). Sea kraits are major colonial predators that are widely distributed in the western Pacific.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, previous genetic investigations suggested spatially oriented sex‐biased dispersal among six colonies of yellow and blue sea kraits ( L. saintgironsi and L. laticaudata ) sampled in New Caledonia; indicating possible geographical genetic structure (Lane & Shine, ). Further, SGS was documented in other marine and terrestrial snake species (Pernetta et al ., ; Lukoschek & Shine, ).…”
Section: Introductionmentioning
confidence: 99%
“…This might be expected if cottonmouths exhibit male‐biased juvenile dispersal and avoid related males during this time to reduce kin competition and inbreeding (Johnson & Gaines, ), as well as the potential for cannibalizing siblings. While cannibalism in cottonmouths has been documented (reviewed by Campbell & Lamar, ), information on dispersal patterns of this species is not available; however, recent genetic studies have found evidence for male‐biased dispersal in several snake species (Rivera, Gardenal & Chiaraviglio, ; Keogh, Web & Shine, ; Clark et al ., ; Dubey et al ., ; Pernetta et al ., ).…”
Section: Discussionmentioning
confidence: 97%